Pengaruh Partisipasi Anggaran Terhadap Efisiensi Kerja Aparat Pemerintah pada Dinas Pemuda, Olahraga, Kebudayaan dan Pariwisata Pemerintah Daerah di Kabupaten Lampung Timur - Rena Agus Rianti; Afridian Wirahadi Ahmad (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2023)
This study aims to determine the effect of budgetary participation on performance efficiency for government officials at the local government Youth, Sports, Culture and Tourism Office in East Lampung district. Obtaining data with the questionnaire method. The sample used was 20 respondents from 25 government officials at the East Lampung Regency DISPORA. The research sample was government apparatus at the East Lampung Regency DISPORA, totaling 8 people. Data was collected using a questionnaire. The formula for the data analysis method is simple variable regression. This research concludes that the significance value is 0.748 > 0.05, so the budgetary participation variable does not have a substantial effect on employee performance. Based on a calculated value of 0.324–2.032 trabels, it means that the budgetary participation variable has no substantial effect on employee performance. So, the results of the study show that budgetary participation does not have a good impact on performance efficiency for government apparatus in DISPORA East Lampung Regency.